Meet the Guest Editor - Bazylak, Grzegorz (Combinatorial Chemistry & High Throughput Screening, 2004)
Dr. Grzegorz Bazylak is currently an associate professor in the Department of Food Sciences & Drug Chemistry, Faculty of Pharmacy, Ludwik Rydygier Medical University (LRMU) in Bydgoszcz, Poland, where he directs research on HTS of potential hypotensive drugs, construction of genosensors, and use of components of edible transgenic plants in drug formulation. He joined this department after completing his D.Sc. (habilitation) in pharmaceutical sciences at the Faculty of Pharmacy, Medical University of Gdansk, Poland, at May 2003, and finishing his intensive research program on the use of supramolecular effects for enhancement of potentiometric detection in HPLC and capillary electrophoresis systems at the Department of Chemistry, University of Antwerpen, Belgium, in course of 2001-2003 years. In this period he was also the visiting scientist and visiting professor, respectively, at the Structural Chemistry Group and Department of Medicinal Chemistry, University of Antwerpen, Belgium, working on the structure-activity relationships of poly(p-phenylene vinylene) oligomers used in construction of electronic nose systems and enantiomeric HPLC separation of small molecule inhibitors of dipeptydyl peptidase IV. In years 1997-2001 he was an adjunct professor at the Department of General Chemistry, Faculty of Medicine, Medical University of Lodz, Poland, conducting research on development and use of helically distorted chiral selectors for the high-throughput enantioselective HPLC of adrenolytic / adrenomimetic drugs and their candidates as well as implementation of screening chromatographic systems which mimics G-protein coupled receptors. In period of 1991-1997 he administered the biochromatographic laboratory and held position of adjunct professor at the Human Nutrition Division, Hygienics Department, Medical University of Lodz, Poland, and carried out analytical research on separation of iridoid glycosides and chemometrically aided characterization of aminoalcohols as the potential lysosomotropic agents and mitochondrial apoptosis inhibitors. In 1997 he shortly visited Department of Applied Chemistry, University of Nagoya, Japan, and in 1996 he was visiting fellow of Centre of Analytical Chemistry at the Imperial College of Science, Technology and Medicine (South Kensington, London, UK). In 1995 he visited Department of Environmental Medicine, Karolinska Institutet, Stockholm, Sweden, extending his knowledge on nutritional epidemiology and biostatistics. In years 1979 - 1991 he worked as the research scientists and finally adjunct professor at the Department of Bioinorganic and Analytical Chemistry, Institute of Fundamental Food Chemistry, Technical University of Lodz, Poland. In this last university he achieved his M.Sc. (1979) and Ph.D. (1990) degree in, respectively, food chemistry and technical sciences. During this pioneering time his research interest lied in the area of the heterogeneity of gas chromatographic adsorbents, synthesis of biomimetic nickel chelates, application of complexation gas chromatography in separation of pyridine-like analytes, quantitation of acroleine in waste animal fats, and HPLC determination of carcinogenic polycyclic aromatic hydrocarbons in mineral oils as part of his collaboration with cosmetic industry. Until today Dr. Bazylak published over 70 scientific papers in the open literature, give more than 60 conference presentations, and compiled 3 chapters in student teaching handbooks. His scientific activity was honored in 2003 by the individual scientific award from the National Ministry of Health, Warsaw, Poland. He serves now as the permanent member of the Establishers Council of the Polish Supramolecular Chemistry Network Foundation (from 1997), and Institutional Coordinator of Socrates-Erasmus Programes in LRMU (from 2003). In 2000 he served as the Guest Editor of special issue of CC In addition, during the years 1998-2001 he was a member of editorial board of three literary journals in Poland, serving as the reviewer of theatre events, and published also four poetry books (in Polish).